Pengujian Kualitas NPK Biofertilizer Dalam Pengolahan Limbah Padat Serat Buah Sawit - Bagus Anugrah; Adrianto Ahmad; David Andrio (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Along with the increase in CPO production, there are still many palm fruit fiber wastes that have not been utilized properly. One alternative to palm fruit fiber waste that is environmentally friendly is by applying the principle of 3R (Reduce, Reuse, Recycle) that is by composting. The composting process can be a strategy for recycling large amounts of sustainable organic waste. The purpose of this study was to determine the effect of POME addition on NPK quality with variations in POME of 0%, 20%, 30%, 40% and measurements were made on N, P, K, pH, water content, temperature, and compost produced compared to the standard the quality of compost SNI 19-7030-2004. In this study composting was carried out by aerobic windrow method. The results showed that the effect of increasing POME gave the best results as indicated by the content with pH 6.99, water content 42.44%, and temperature 32.06 0C. The highest quality of N elements and in accordance with SNI 19-7030-2004 is the addition of POME 20% which is equal to 2.61%. The highest quality of P and K elements is by adding POME 40% which is equal to, 1.1%, and 3.09% with composting time for 25 days. Thus the utilization of palm fruit fiber as compost is one of the solutions to sustainable environmental pollution control.Keywords : Composting, NPK, Palm Fruit Fiber, Palm Oil Mill Effluent (POME), Windrow.